Risk Factors for Lymph Node Metastasis in Papillary Thyroid Carcinoma: A Retrospective Study - Gong, Jiantao; Zhu, Baining; Liu, Wenji; Shi, Chaoqun; Xia, Chen; Zeng, Liqin; Lv, Yunxia (Hormone and Metabolic Research, 2023)
At present, the risk factors of cervical lymph node metastasis (LNM) in papillary thyroid carcinoma (PTC) are still controversial. This study was aimed to investigate the risk factors of various types of LNM in PTC with tumor diameter>1 cm. The clinical data of 2216 PTC patients were retrospectively analyzed. Univariate and multivariate logistic regression models were used to analyze the risk factors of LNM. In addition, the receiver operator characteristic (ROC) curve was used to find the best cut-off value of CLNM for predicting LLNM. Finally, the independent risk factors of LLNM were used to construct the prediction of LLNM nomogram. Age≤55 years old, male, bilateral lobe tumors, ETE, 2–3 cm tumor diameters, and fasting plasma glucose (FPG) were independent risk factors for CLNM. The ROC curve showed that the best cut-off value was 2.5. Age, male, bilateral lobe tumors, tumor diameters≥2 cm and CLNM≥3 were significantly associated with LLNM , while CLNM=1 or 2 was a protective factor for LLNM. Only tumor diameters≥3 cm was significantly associated with skip LLNM. The nomogram model (C-index=0.745) can be used to predict LLNM in PTC patients and guide the clinical selection of appropriate treatment options. Patients with high risk factors should undergo prophylactic lymph node dissection. The nomogram we established has a good predictive ability for LLNM, and for high-risk groups, it is necessary to actively perform prophylactic lateral lymph node dissection.
Keywords: papillary thyroid carcinoma; lymph node metastasis; risk factor; prognosis